The mediating effect of burnout on the relationship between workplace culture and intent to stay among registered nurses in Saudi Arabia - Mesheil Alalyani; Joyce Buta; Benito Areola Jr; Ohoud Naif Aldughmi; Ingrid Jacinto-Caspillo; Sumathi Robert Shanmugam; Richard Maestrado; Allen Joshua Dominguez; Analita Gonzales; Nuha Ayad H. Alatawi; Romeo Mostoles; Reem Humaidi Alalawi; et al. (PLoS ONE, 2026)
Background Nurse turnover is a critical challenge to healthcare quality in Saudi Arabia, yet the mechanisms linking workplace culture to retention intentions remain unclear. While workplace culture and burnout have each been associated with turnover intentions, no study in the Saudi nursing context has examined whether burnout operates as an intermediary mechanism through which workplace culture influences nurses’ decisions to stay. Grounded in the Job Demands-Resources model, this study tested whether burnout mediates the relationship between workplace culture and intent to stay among registered nurses in Saudi Arabia. Methods A cross-sectional, correlational design was employed. The sample comprised 355 full-time registered nurses from five Ministry of Health hospitals in the Hail and Qassim regions of Saudi Arabia. Nurses were selected using proportionate stratified random sampling, with geographic region and hospital as stratification factors. The population of 2,500 nurses was divided into two regional strata; 240 nurses were randomly selected from Hail (three hospitals) and 160 from Qassim (two hospitals), proportional to the nurse population in each region. Data were collected via self-administered online surveys (Google Forms) from November 15, 2025, to January 15, 2026. Workplace culture was measured with the Organizational Culture Survey, burnout with the Copenhagen Burnout Inventory, and intent to stay with the Intent to Stay Scale. Structural equation modeling with bootstrapping (5,000 samples) was used to test the mediation hypothesis. Results Participants reported moderate perceptions of workplace culture (M = 2.88, SD = 0.73), high burnout (M = 3.58, SD = 0.65), and low intent to stay (M = 2.66, SD = 0.67). Workplace culture was negatively correlated with burnout (r = −0.34, p < .001) and positively correlated with intent to stay (r = 0.57, p < .001). Burnout was negatively correlated with intent to stay (r = −0.43, p < .001). In the SEM, workplace culture had a significant direct effect on intent to stay (β = 0.48, p < .001). The indirect effect of workplace culture on intent to stay through burnout was significant (β = 0.09, 95% CI [0.05, 0.16], p < .001), indicating partial mediation. The model explained 11.6% of the variance in burnout and 38.9% of the variance in intent to stay. Model fit was mixed: RMSEA and SRMR indicated good fit, while CFI and TLI were marginal (χ²(412) = 847.32, χ²/df = 2.06, CFI = 0.94, TLI = 0.93, RMSEA = 0.055 [90% CI 0.050, 0.060], SRMR = 0.048). Conclusion In this cross-sectional study of Saudi nurses, workplace culture was associated with intent to stay through both a direct association and an indirect association via burnout. These findings are consistent with the Job Demands-Resources model and suggest that workplace culture and burnout are co-occurring factors related to retention attitudes.